A 12-year analysis of closed medical malpractice claims of the Taiwan civil court: A retrospective study. Issue 13 (March 2018) - Hwang, Chi-Yuan; Wu, Chien-Hung; Cheng, Fu-Cheng; Yen, Yung-Lin; Wu, Kuan-Han
Abstract : Abstract: Malpractices lawsuits cause increased physician stress and decreased career satisfaction, which might result in defensive medicine for avoiding litigation. It is, consequently, important to learn experiences from previous malpractice claims. The aim of this study was to examine the epidemiologic factors related to medical malpractice claims, identify specialties at high risk of such claims, and determine clinical which errors tend to lead to medical malpractice lawsuits, by analyzing closed malpractice claims in the civil courts of Taiwan. The current analysis reviewed the verdicts of the Taiwan judicial system from a retrospective study using the population-based databank, focusing on 946 closed medical claims between 2002 and 2013. Among these medical malpractice claims, only 14.1% of the verdicts were against clinicians, with a mean indemnity payment of $83, 350. The most common single specialty involved was obstetrics (10.7%), while the surgery group accounted for approximately 40% of the cases. In total, 46.3% of the patients named in the claims had either died or been gravely injured. Compared to the $75, 632 indemnity for deceased patients, the mean indemnity payment for plaintiffs with grave outcomes was approximately 4.5 times higher. The diagnosis groups at high risk of malpractice litigation were infectious diseases (7.3%), malignancies (7.2%), and limb fractures (4.9%). A relatively low success rate was found in claims concerning undiagnosed congenital anomalies (4.5%) and infectious diseases (5.8%) group. A surgery dispute was the most frequent argument in civil malpractice claims (38.8%), followed by diagnosis error (19.3%). Clinicians represent 85.9% of the defendants who won their cases, but they spent an average of 4.7 years to reach final adjudication. Increased public education to prevent unrealistic expectations among patients is recommended to decrease frivolous lawsuits. Further investigation to improve the lengthy judicial process is also necessary to relieve the stress of medical malpractice claims on clinicians and practitioners, as well as on the judicial system and rightful claimants.